2023
DOI: 10.1097/spv.0000000000001344
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Urinary Retention

Abstract: This clinical consensus statement on the management of postoperative (<6 weeks) urinary retention (POUR) reflects statements drafted by content experts from the American Urogynecologic Society's POUR writing group. The writing group used a modified Delphi process to evaluate statements developed from a structured literature search and assessed for consensus. After the definition of POUR was established, a total of 37 statements were assessed in the following 6 categories:(1) incidence of POUR, (2) medications,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 128 publications
(373 reference statements)
0
5
0
Order By: Relevance
“…Delayed postoperative urinary retention is a rare complication that can cause patients to have severe pain and require an urgent visit for catheter placement. 3 Identifying patients at risk would be helpful for clinicians, but there are few identifiable risk factors outside of the initial postoperative voiding trial. A standardized assessment would be key in future studies to determine what these risk factors are.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Delayed postoperative urinary retention is a rare complication that can cause patients to have severe pain and require an urgent visit for catheter placement. 3 Identifying patients at risk would be helpful for clinicians, but there are few identifiable risk factors outside of the initial postoperative voiding trial. A standardized assessment would be key in future studies to determine what these risk factors are.…”
Section: Discussionmentioning
confidence: 99%
“…No specific PVR or voided volume measurement has been proven to be superior in the literature; thus, the criteria for passing voiding trials varied widely. 3 These differing criteria may affect our results in that no universal protocol was followed, which limits our ability to determine which method is better for detecting postoperative urinary retention. To account for these varying definitions of voiding trial failure and the multitude of variables, two primary outcomes were identified to better quantify a passed compared with failed trial of void.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations